2018
DOI: 10.1097/igc.0000000000001335
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Outcomes of Venous Thromboembolism in Hospitalized Patients With Ovarian Cancer: Results From Nationwide Inpatient Sample Database 2003 to 2011

Abstract: Venous thromboembolism in hospitalized patients with ovarian cancer is associated with higher inpatient mortality, length of stay, higher cost of hospitalization, and disability at discharge. The hospitalization rate has increased, but the inpatient mortality rate has declined over study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…VTE is a serious complication in intravenous therapy. VTE can increase the length of hospitalizations, costs and mortality (Devani et al,2017;Lyman et al,2018;Mittal et al,2018). In the US subgroup, the meta-analysis showed that the prevalence of VTE with MCs was higher than that with PICCs (RR=1.50, 95% CI: 1.30-1.73, p <.00001).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…VTE is a serious complication in intravenous therapy. VTE can increase the length of hospitalizations, costs and mortality (Devani et al,2017;Lyman et al,2018;Mittal et al,2018). In the US subgroup, the meta-analysis showed that the prevalence of VTE with MCs was higher than that with PICCs (RR=1.50, 95% CI: 1.30-1.73, p <.00001).…”
Section: Discussionmentioning
confidence: 98%
“…VTE is a serious complication in intravenous therapy. VTE can increase the length of hospitalizations, costs and mortality (Devani et al.,2017; Lyman et al.,2018; Mittal et al.,2018). The prevalence of VTE was different with different VADs.…”
Section: Discussionmentioning
confidence: 99%
“…Overall rates of VTE‐associated hospitalisations were not reported, making it difficult to place the findings in the context of general time trends in the NIS population. Increasing hospitalisations for VTE have been described within the NIS population over a comparable period (2003–2013), 2 and other condition‐specific studies have reported a rise 3,4 . The reported increase in the rate of VTE was seen in base‐case analysis, where all elective or emergent admissions with codes for IBD and VTE were included.…”
mentioning
confidence: 93%
“…Increasing hospitalisations for VTE have been described within the NIS population over a comparable period (2003-2013), 2 and other condition-specific studies have reported a rise. 3,4 The reported increase in the rate of VTE was seen in base-case analysis, where all elective or emergent admissions with codes for IBD and VTE were included. A condition-specific sensitivity analysis, restricted to emergency cases with a primary diagnosis of IBD, revealed no such rise.…”
mentioning
confidence: 99%